Impacts of external shocks and domestic change on Thailand’s economy and social policies - Natenapha Wailerdsak; Akira Suehiro (Journal of Contemporary East Asia Studies)
This article examines the impacts on Thailand’s economy and social policies of external shocks, especially the 1997 Asian financial crisis (AFC), Global Financial Crisis (GFC), and coronavirus disease 2019 (COVID-19) pandemic, in addition to domestic political and societal movements. It points out that in Thailand as well as some Asian countries, there are three threats exposed by the COVID-19 pandemic, including the globalization of the world economy, the growth of international migrant workers, and the tertiarization of the economy. Crisis-induced economic downturns leave many unemployed and lower living standards. Governments intervene to mitigate social and political risks and retain public support. This greatly improved social policy. This study will examine the social security system, focusing on worker protection during crises, such as unemployment insurance, universal health coverage, and employment-related legislation. Normal circumstances would make progress on these concerns difficult, especially in developing nations like Thailand where worker collective bargaining power is severely curtailed. The paper concludes that both external shocks and domestic change accelerated the social policy shifts and their challenge in a more egalitarian society of a latecomer industrialized nation.